Treating dental crowding with mandibular incisor extraction in an Angle Class I patient - Machado, Gislana Braga (Dental Press J Orthod, 2015)
Mandibular dental crowding often encourages patients to seek orthodontic treatment. The orthodontist should decide between protrusion of incisors or decrease in dental volume so as to achieve proper alignment and leveling. The present study reports the treatment of an Angle Class I malocclusion adolescent female brachyfacial patient with severe mandibular dental crowding, increased curve of Spee and deep overbite. The patient was treated with extraction of a mandibular incisor. This case was presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO) as a requirement for the title of certified by the BBO.